Encephalitis, Mild Encephalitis, Neuroprogression, or Encephalopathy—Not Merely a Question of Terminology - Bechter, Karl (Frontiers in Psychiatry, 2019)
Meningoencephalitis and encephalitis are comparably well-defined clinical terms in neuropsychiatry, although in the individual case approach diagnosis can be difficult, for example some cases of encephalitis described with normal cerebrospinal fluid findings, or often in chronic encephalitis. Encephalopathy is also a widely accepted term, however with a surprisingly broad meaning with regard to the assigned underlying pathophysiology, ranging from one- hit traumatic encephalopathy to inflammatory encephalopathy, the latter a type of brain dysfunction secondary to acute systemic inflammation without proven brain autochthonus inflammation , ie. neuroinflammation. However, this latter assumption may be wrong as neuroinflammation is difficult to prove in vivo. With emerging insights into prevailing inflammatory and neuroinflammatory mechanisms to be involved in the pathogenesis of severe mental disorders, the interdependent question of sensitive assessment and clinical relevance of mild neuroinflammation is of increasing interest. The traded clinical terms and the newly proposed terms of mild encephalitis, parainflammation and neuroprogression are therefore reconsidered here with regard to emerging clinical relevance and respective borders, gaps and overlap in between. Categorical delineation of the terms with respect to individualised psychiatric treatment is required and preliminary attempted here on the basis of available data.